2016
DOI: 10.3390/ijms17091445
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Zinc Sulfate Results in Differential Effects on Olfactory Sensory Neuron Subtypes in Adult Zebrafish

Abstract: Zinc sulfate is a known olfactory toxicant, although its specific effects on the olfactory epithelium of zebrafish are unknown. Olfactory organs of adult zebrafish were exposed to zinc sulfate and, after 2, 3, 5, 7, 10 or 14 days, fish were processed for histological, immunohistochemical, ultrastructural, and behavioral analyses. Severe morphological disruption of the olfactory organ was observed two days following zinc sulfate exposure, including fusion of lamellae, epithelial inflammation, and significant lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…Unlike the results of existing studies on mice, so far, only GAP-43 has been identified as an iOSN histochemical antigen for fish 32 , 33 . It turns out that calretinin, which is typically present in iOSNs of mice 30 , colours only mature OSNs in fish and may be observed at varying extents in ciliated, microvillar and crypt OSNs 34 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the results of existing studies on mice, so far, only GAP-43 has been identified as an iOSN histochemical antigen for fish 32 , 33 . It turns out that calretinin, which is typically present in iOSNs of mice 30 , colours only mature OSNs in fish and may be observed at varying extents in ciliated, microvillar and crypt OSNs 34 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The fish olfactory sensory epithelium (OE) is in direct contact with the aquatic environment, and thus it is particularly vulnerable to exposure to waterborne pollutants, chemical toxicants, and direct injury. Damage to the olfactory system can impair olfactory function through various mechanisms affecting its different components: (1) by acting as olfactory signals (i.e., binding directly to ORs and reducing sensing of odorants) [6]; (2) by reducing odor perception and processing (e.g., through OSN injury or death) [19]; and (3) by affecting odor-dependent behaviors (e.g., reducing social behaviors) [95]. The effects of toxicants and injury on olfactory organ morphology can be studied by assessing tissue and cellular alterations through histological, immunohistochemical, and ultrastructural techniques.…”
Section: The Olfactory System Of Zebrafish As a Model Of Neuroplasmentioning
confidence: 99%
“…Given that odors mediate behaviors essential for survival, the olfactory system is equipped with wide-ranging neuroplasticity, remodeling, and regeneration mechanisms following damage [3,4,5,18,19,20], thus making it an excellent model to study repair responses following toxicant exposure and injury. In this section, we review results from several studies that have addressed the impact of a variety of toxicants, as well as the morphological and behavioral effects of chemical and physical lesioning on the olfactory system of zebrafish, as well as regeneration and repair mechanisms following damage.…”
Section: The Olfactory System Of Zebrafish As a Model Of Neuroplasmentioning
confidence: 99%
See 2 more Smart Citations